EFFECTS OF ACCOUNTING TOOLS ON SOCIAL AND ENVIRONMENTAL ACCOUNTING - Tan Oscario Archie Kristandy; Frank Gruben (Diponegoro Journal of Accounting, 2021)
The purpose of this paper is to analyze and evaluate how True Value and Social Value methodologies affect the company's performance, which aims to measure in financial terms the value firms make or decrease for social and environmental reasons. True Value and Social Value methodology to scrutinise social and environmental externalities and their potential effect on future earnings the consequence that management action may result in more positive social and environmental impacts may easily become a by-product of risk management rather than an objective.